Multiple ecosystem services of monoculture and mixed plantations: A case study of the Huitong experimental forest of Southern China. (December 2018) - Dai, Erfu; Zhu, Jianjia; Wang, Xiaoli; Xi, Weimin
Highlights: Ecosystem services that provided by monocultures and mixed plantations were compared using InVEST model. None of the types of forests were found to always have a high level of multiple ecosystem services. Plantation management should increase the amount of mixed plantations rather than monocultures. Abstract: With the expansion of plantations all over the world, there are increasingly more concerns about their ability to support multiple ecosystem services. We hypothesized that mixed plantations with a high number of tree species could provide a higher level of ecosystem services than monocultures. To test this hypothesis, we selected the experimental forest of the Huitong National Research Station of Forest Ecosystem as our study area and applied the Integrated Valuation of Ecosystem Services and Tradeoffs Model (InVEST) and the Integrated Water Storage Capacity Model to evaluate five types of ecosystem services (timber production, water provision, carbon storage, soil conservation, and water retention) provided by plantations and natural forests. None of the plantations or natural forests were found to have a constantly high level of multiple ecosystem services. The results showed that the overall benefits of the ecosystem services were highest in mixed plantations, followed by coniferous plantations and broadleaf plantations. Natural forests in our study had relatively high values of regulating services. These findings suggest that plantation management should increase the number of mixed plantations rather than monocultures. In addition, the future protection of natural forests requires urgent consideration.